Bulk Oxygen Stabilization via Electrode‐Electrolyte Interphase Tailored Surface Activities of Li‐Rich Cathodes. Issue 2 (23rd November 2022) - Zhang, Xu; Zhao, Jingteng; Lee, Gi‐Hyeok; Liang, Yuan; Wang, Boya; Liu, Shiqi; Wang, Errui; Yang, Wanli; Yu, Haijun
Abstract: The O3‐type Li‐rich layered oxides (LLOs) are approaching industrial applications as high‐energy cathode materials for Li‐ion batteries (LIBs), however, they suffer from rapid performance decay associated with oxygen activities. The interplay between surface and bulk transformations in LLOs, especially the electrochemical behaviors of oxygen anions, remains elusive. Here, by regulating the surface of an O3‐type LLO (Li1.13 Mn0.517 Ni0.256 Co0.097 O2 ) using an all‐fluorinated electrolyte, an enhanced capacity retention from 57.4% to 85.3% and a suppressed voltage decay from 1.34 mV cycle −1 to 0.58 mV cycle −1 within 300 cycles are realized. The performance enhancement is attributed to the thin, uniform, robust, and compact F‐rich cathode‐electrolyte interphase (CEI), which suppresses various types of oxygen‐related surface degradation and, more importantly, stabilizes the bulk oxygen reactions. Through the combined experimental and theoretical studies, this work directly reveals the intriguing association between the surface and bulk oxygen activities and demonstrates that optimizing the interphase is an effective approach for improving the stability of high‐energy battery cathodes involving oxygen redox reactions. Abstract : An F‐rich cathode‐electrolyte interphase (CEI) is in situ constructed to improve the initial Coulombic efficiency and capacity/voltage retention of an O3‐type lithium‐rich layered oxide cathode material in lithium‐ion batteries. The surface oxygen stabilized by the F‐rich CEI further stabilizes the bulk oxygen by reducing the concentration gradient and thus enhances the reversibility of oxygen anionic redox.